2023
DOI: 10.3847/1538-4357/accc32
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Collisional Analysis of Solar Wind Ions

Abstract: Owing to its low density and high temperature, the solar wind frequently exhibits strong departures from local thermodynamic equilibrium, which include distinct temperatures for its constituent ions. Prior studies have found that the ratio of the temperatures of the two most abundant ions—protons (ionized hydrogen) and α-particles (ionized helium)—is strongly correlated with the Coulomb collisional age. These previous studies, though, have been largely limited to using observations from single missions. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Maruca et al (2013) applied this technique to individual θ αp -measurements from the Wind spacecraft (r = 1.0 au) to predict the distribution of θ αp -values at r = 0.1 au, i.e., near-Sun solar wind. This prediction was confirmed by Johnson et al (2023), who further validated the collisional analysis technique by showing that it could be applied to θ αp -measurements from Parker Solar Probe (PSP; r = 0.1-0.27 au) to effectively predict contemporaneous measurements of θ αp from Wind.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Maruca et al (2013) applied this technique to individual θ αp -measurements from the Wind spacecraft (r = 1.0 au) to predict the distribution of θ αp -values at r = 0.1 au, i.e., near-Sun solar wind. This prediction was confirmed by Johnson et al (2023), who further validated the collisional analysis technique by showing that it could be applied to θ αp -measurements from Parker Solar Probe (PSP; r = 0.1-0.27 au) to effectively predict contemporaneous measurements of θ αp from Wind.…”
Section: Introductionmentioning
confidence: 73%
“…The data set used in this study is the same as the one used by Johnson et al (2023), who provide a detailed discussion of its properties and of the algorithm applied to correct for variations in sampling cadence. The data were derived from ion measurements from the electrostatic analyzer (ESA; Livi et al, 2021) in the SWEAP instrument suite (Kasper et al, 2016) onboard the PSP spacecraft (Fox et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high R b and high ε r are likely tied to each other, and, depending on their cause, could also be driving up χ 2 /dof values. Recent work by Johnson et al (2023) has shown, using PSP and Wind data, that the preferential heating of alpha particles persists up to about 0.27 au, beyond which Coulomb collisions provide the dominant thermalizing effect. While this is lower than the alpha-particle result shown here with SWICS data, it is within the range of SWICS R b predictions for ions with a q/m of about 0.5.…”
Section: Discussionmentioning
confidence: 99%